Pregnancy outcome in obstetric cholestasis of pregnancy with active management - Singh Shrestha, Nira; Panta, Sajipta (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To study the maternal and perinatal outcome of pregnancies complicated with obstetric cholestasis with active management. Methods: This is a cross- sectional, descriptive study done at the department of obstetrics and gynecological of KMCTH for 24 months. All the cases of obstetric cholestasis that were managed by active management were enrolled as cases. Their demographic details, maternal and perinatal outcome were noted. Data was analyzed and presented as mean, percentage and frequency and presented as tables and figures. Results: Total 84 cases of obstetric cholestasis were managed by active management during the study period. The mean age of the women were 26.59 years (21-34 years), the mean gestational age at diagnosis was 32.53 weeks (18 - 38 weeks). Diabetes mellitus was present in 17.85% and15.47% % had hypertensive disorder of pregnancy. All the cases had complaint of pruritus and 89.25% of the case had itching over abdomen, 73.78% of the women had itching over palms and soles. The itching was severe enough to cause sleep disturbance in over 65% of the cases. Meconium staining of liquor was present in 17.85% of the cases; cesarean section rate was 60.69%. There were 3 cases (3.57%) of postpartum hemorrhage but none required blood transfusion. There were no cases of still birth or neonatal death. Over 10% of the neonate had Apgar score less than 7 at 5 minute and approximately one fourth of the newborn required NICU care. Conclusions: Adverse pregnancy outcome associated with obstetric cholestasis can be minimized with active management of the cases.